Evaluation of the inhibitory effects of pyridylpyrazole derivatives on lps-induced pge2 productions and nitric oxide in murine raw 264.7 macrophages - El-Din, M.M.G.; El-Gamal, M.I.; Kwon, Y.-D.; Kim, S.-Y.; Han, H.-S.; Park, S.-E.; Oh, C.-H.; Lee, K.-T.; Kim, H.-K. (MDPI, 2021)
A series of thirteen triarylpyrazole analogs were investigated as inhibitors of lipopolysaccharide (LPS)-induced prostaglandin E2 (PGE2 ) and nitric oxide (NO) production in RAW 264.7 macrophages. The target compounds 1a？m have first been assessed for cytotoxicity against RAW 264.7 macrophages to determine their non-cytotoxic concentration(s) for anti-inflammatory testing to make sure that the inhibition of PGE2 and NO production would not be caused by cytotoxicity. It was found that compounds 1f and 1m were the most potent PGE2 inhibitors with IC50 values of 7.1 and 1.1 ？M, respectively. In addition, these compounds also showed inhibitory effects of 11.6% and 37.19% on LPS-induced NO production, respectively. The western blots analysis of COX-2 and iNOS showed that the PGE2 and NO inhibitory effect of compound 1m are attributed to inhibition of COX-2 and iNOS protein expression through inactivation of p38. ？ 2021 by the authors. Licensee MDPI, Basel, Switzerland.